Manajemen Pembiayaan dalam Mendukung Kegiatan Pengembangan Bakat Peserta Didik di MIS As-Salafiyah Sumber Duko Pamekasan - Wahidah, Romlatul; Aziz, Abdul (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2025)
This study aims to analyze financing management in supporting talent development activities at MIS As-Salafiyah Sumber Duko Pamekasan. The research focuses on how the school allocates, utilizes, and monitors educational funds to support programs such as Pramuka, Qiro’ah, and Tahfidz Juz 30. Using a qualitative descriptive approach, data were collected through interviews, documentation, and observation. The findings reveal that financing management is carried out through planned budgeting, prioritization of needs, transparency, and accountability in fund use. Well-managed financing contributes significantly to the continuity and quality of talent development programs. Moreover, the provision of training materials, competent instructors, rewards, and facility support all rely on effective financial planning. This study highlights the importance of financial governance in enhancing student’s talents and supporting holistic educational goals.